Free to move: The costs and consequences of restrictions on migration - Philippe Legrain (Institute of Economic Affairs (IEA), 2016)
Immigration is perhaps the most controversial political issue in Britain today. It is a key reason why 52 per cent of Britons voted to leave the European Union in June 2016. Yet negative misperceptions about migration abound. People greatly overestimate the immigrant share of the population and many wrongly believe that openness to migration harms Britons' job prospects, burdens public finances and services and makes housing prohibitively expensive. Openness to migration actually brings big economic benefits. These stem primarily from the very thing that makes immigration so controversial: the fact that migrants are different - with diverse attributes, skills, perspectives and experiences that tend to complement ever-changing local resources, needs and circumstances. Migration is, in effect, a form of international trade which similarly raises productivity and living standards. Indeed, static analysis understates its dynamic boost to productivity growth. By raising the diversity of skills and ideas at the economy's disposal and spurring entrepreneurial activity, it enhances economic dynamism. The UK government ignores this evidence and seeks to restrict net migration to 'tens of thousands' of people a year. Citizens from outside the European Economic Area (EEA) must meet elaborate conditions to obtain a work, student, family, refugee or other visa from the government. The work visa tiers in particular are arbitrary and absurd, with government officials second-guessing the needs of the economy and migrants' future economic contribution. Just as free trade is economically optimal, economic theory and evidence suggest that the first-best economic policy for migration is freedom of movement. This currently works successfully for EEA citizens and could be expanded, with limited exceptions such as known terrorists, agents of hostile foreign governments and those carrying highly infectious dangerous diseases. Free movement to work does not imply immediate citizenship or voting rights. Sweden's labour migration policy is a good second-best compromise. Companies based there are able to hire people of all skill levels from anywhere in the world on two-year renewable visas, with no limit on entry numbers. It is an open, flexible and non-discriminatory system, which reassures voters that migrants are coming only to work. At the very least, the target to lower net migration should be scrapped, as should the quotas on Tier 1 and Tier 2 visas, in favour of a skillsneutral work-permit system. Trade theory is instructive on how to build a more liberal migration system pragmatically. While removing all migration restrictions unilaterally is optimal, agreeing bilateral two-way free-movement deals with other countries could help assuage domestic protectionist instincts and raise the political cost of erecting future trade barriers. Even if Britain leaves the EEA, it should maintain bilateral free movement with the block. Britain could also aim to conclude free-movement deals with countries such as Australia and New Zealand (where political opposition is likely to be smallest) and seek to extend such reciprocal agreements more widely. The visa process for citizens of other countries should also be reformed. Work visas should be granted automatically to those with a job offer and student visas granted to anyone registering for a UK education course. Foreign students should be free to remain following their studies. Asylum seekers could be allowed to work while their asylum claims are processed, minimising their initial fiscal cost and fast-tracking their entry into the labour market and society. Associated reforms to help defuse the political backlash to migration could include moves towards a more contributory welfare system (or at least denying migrants access to welfare benefits initially), enhancing the efficiency and flexibility of public-service delivery, and reforming land-use planning to make the housing market and infrastructure development more responsive to demand.
Keywords: 330